Strategy Of Developing Tiku Beach As A Marine Tourism Destination In Tanjung Mutiara District, Agam Regency - Husna, Rifdatul; Zengga, Zengga; Sari, Windy Della (SEAN Institute, 2024)
Purpose This study aims to analyze the tourism development strategy of Tiku Beach by using the 4A components (attraction, accessibility, amenity, and ancillary services) as marine tourism in Tanjung Mutiara District, Agam Regency, It is expected that after this research is conducted, the resulting model for marine tourism development can be implemented and applied for developing other areas in the future. The study employs a descriptive qualitative research design. Data were collected through observation, in-depth interviews, and document studies. The data were analyzed using SWOT analysis, EFAS, and IFAS matrices to formulate an appropriate development strategy based on the findings. The SWOT analysis of the 4A components shows that a growth-oriented strategy is most suitable for Tiku Beach. This strategy utilizes existing strengths to support opportunities for aggressive growth in the tourism sector. This study offers actionable insights that can enhance the strategic position and efficiency in developing marine tourism at Tiku Beach. These insights can be applied by tourism managers (Pokdarwis) and the local community to economically benefit and improve the living standards in the region,